1997
DOI: 10.1128/jcm.35.10.2670-2672.1997
|View full text |Cite
|
Sign up to set email alerts
|

Natural transmission of Pneumocystis carinii in nonimmunosuppressed animals: early contagiousness of experimentally infected rabbits (Oryctolagus cuniculus)

Abstract: Airborne transmission of Pneumocystis carinii has been established, but the infective form and the sources of infection remain unknown. Animal models for studies of P. carinii have previously been limited to immunosuppressed rodents; however, this study was performed with nonimmunodepressed P. carinii-free rabbits. This study was aimed at determining (i) the delay between inoculation of animals (day zero [D0]) and the onset of contagiousness and (ii) the end of contagiousness of these animals (donors). Five-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The results indicated that P carinii was transmitted between pigs by aerosol, but not vertically, although the infection was demonstrated in young suckler pigs. The airborne transmission of P carinii has been reported in rats, rhesus macaques and rabbits (Hughes 1982, Vogel and others 1993, Cere and others 1997). There was no transmission via the placenta even in heavily infected mice (Ito and others 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that P carinii was transmitted between pigs by aerosol, but not vertically, although the infection was demonstrated in young suckler pigs. The airborne transmission of P carinii has been reported in rats, rhesus macaques and rabbits (Hughes 1982, Vogel and others 1993, Cere and others 1997). There was no transmission via the placenta even in heavily infected mice (Ito and others 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of Pneumocystis species DNA in twin stillborn marmosets ( Callithrix jacchus ) suggested that vertical transmission of Pneumocystis species may occur in non‐human primates. This mode of transmission was ruled out in mice (Ito and others 1991) but is suspected in human beings (Mortier and others 1995) and has been proved in rabbits (Ceré and others 1997).…”
Section: Characteristics Of Animals Number Of Animals Number (%) Of Pmentioning
confidence: 96%
“…The lungs were finely minced, homogenised by crushing and subjected to sequential membrane filtration (Ceré and others 1997). The final filtrates were used for direct examination and DNA extraction.…”
Section: Characteristics Of Animals Number Of Animals Number (%) Of Pmentioning
confidence: 99%
“…Although less commonly used than rodents, studies of rabbits infected by P. oryctolagi have revealed some distinct features. Compared to rodents, healthy rabbits can develop relatively heavy Pneumocystis infection either spontaneously at weaning or following cohousing with infected rabbits ( 19 , 20 ). This spontaneous, natural infection is usually resolved within 3–4 weeks.…”
Section: Discussionmentioning
confidence: 99%